Business Process Analysis and Implementation of Odoo Open Source ERP System in Inventory, Purchasing and Sales Activities : Analisis Proses Bisnis dan Penerapan Sistem ERP Odoo Open Source Pada Aktivitas Persediaan, Pembelian dan Penjualan - Aditya, Addin; Efendi, Hamzah Fatoni (Procedia of Social Sciences and Humanities, 2022)
The development of information technology is the main thing for trading companies in developing their business. Resources within the company must be managed and utilized optimally, one of which is inventory, buying and selling of goods. ERP (enterprise resource planning) system is an integrated information system concept that can be utilized by companies and SMEs (micro, small and medium enterprises) to improve company performance. Captain Gadget is one of the medium-sized businesses engaged in retail sales of mobile phones, mobile accessories and spare parts for mobile phones, which is located in Malang City. Captain Gadget has three employees who run its core business. In the procurement of goods, it is carried out by the procurement admin, in the management of stock goods it is carried out by the warehouse admin and in sales it is carried out by the sales department. The company in processing its data using Microsoft Excel application, while the recording and bookkeeping of cash is done manually. This causes less effective and efficient performance. For this reason, it is necessary to configure and implement an ERP (enterprise resource planning) system to support business process activities on the Captain gadget. One of them is using Odoo ERP software based on Open Source which can be adapted to the system needs in business processes at Captain Gadget.